Micro- and nanoplastics in periodontitis: mechanistic pathways and clinical implications - Bharathi Ganesan; Nina Shenoy (Frontiers in Dental Medicine, 2026)
Micro- and nanoplastics (MNPs) are increasingly recognized as pervasive environmental contaminants with potential relevance to oral and periodontal health. The oral cavity is continuously exposed to MNPs through water, food, air, oral-care products, and polymer-based dental materials, placing periodontal tissues at a plausible interface between environmental exposure and chronic inflammation. Emerging evidence suggests that MNPs can aggravate biologic processes central to periodontitis, including oxidative stress, mitochondrial dysfunction, inflammatory signaling, epithelial barrier disruption, dysbiosis, inflammasome activation, and imbalanced bone remodeling. MNPs may also act as colonization surfaces for biofilm development, alter microbial selection pressures, and contribute to antibiotic resistance gene enrichment, although direct evidence for an oral plastisphere remains limited. Epigenetic changes, including altered DNA methylation, histone marks, and microRNA profiles, provide an additional mechanism by which MNP exposure may sustain inflammatory priming. Current evidence remains predominantly preclinical, and contamination-controlled studies directly quantifying oral MNP burden in relation to periodontal phenotype are still lacking. This review summarizes current evidence on oral exposure pathways, mechanistic links between MNPs and periodontal breakdown, translational implications, and priorities for future research. Present data support viewing MNPs as plausible environmental modifiers of periodontitis rather than established independent causal agents.